Mitologija in Tolkienov Hobit - Artnik, Gregor (Revija za elementarno izobraževanje, 2009)
Mytology in Tolkien's The Hobbit. The paper focuses on identifying the effects of mythology in the three main fantasy novels by J. R. R. Tolkien, one of the more visible authors and pioneers in the field of modern fantasy. The focus is on youth fantasy, namely The Hobbit, searching for its roots in our primary world and finding links to the mythology, which is often not of English origin. Furthermore, it looks into the elucidation of ingrained Christian ideas, which among others also appear in English literature, particularly in times of the great national distress which was caused by the pre-war and anti-human beliefs of the era. Many experts commented that Tolkien's Middle-Earth probably represented the image of a dirty, industrialized and discouraging reality, which in this respect cannot be entirely credible and certainly not the only option to choose from. It soon became evident that many sources were used for the creation of the new mythology. However, the apparent complexity also hides some simplicity, presenting the ups and downs of mankind's gradual steps from the beginning all the way to eternity, and certainly not only to the time of the Second World War. Tolkien's mythology of the fantasy world is not only impressive in terms of its innovation, but reaches out much further than that, sharing higher values which come in useful for the existence of both, the primary world, e.g. humanity in general, as well as the secondary, surreal dimension and its inhabitants.